Calcium absorption effectiveness of prebiotics is affected by the nutritional status of vitamin D - Zeni, Susana Noemi (2017)
Vitamin D (VD) regulates Ca absorption (Abs) which is positively affected by prebiotics through lowering intestinal pH and increasing colonic cells growth. VD insufficiency could affect prebiotic effectiveness on CaAbs. Galactooligosaccharides/Fructooligosaccharides (GOS/FOS®) effectiveness to increase CaAbs was evaluated in an experimental model of VD insufficiency and established osteopenia. Ovariectomized Wistar rats fed a VD-free (0 IU%) diet to become VD insufficient (-D) (n=32) or a normal VD diet (100 IU%) (+D) (n=16), during 45 days. Thereafter, for an additionally 45-days period D+ fed: AIN´93 (control diet) (+D0.5%); AIN´93 containing 0.3%Ca or 2.5%GOS/FOS® (9:1) (+D0.3%P) while D- fed: VD free-AIN´93 (-D0.5%); VD free-AIN´93 containing 0.3%Ca (-D0.3%); last diet containing 2.5% (-D0.3%P) or 5% GOS/FOS (-D0.3%:2xP). Food intake and faeces (F) were collected for CaI and CaF and CaAbs% calculated . Results CaAbs% (mean±SD):.-D0.5%: 32.71±1.74; -D0.3%: 38.33±2.33; -D0.3%P: 44.71±1.84; -D0.3%x2P: 56.40±1.39; +D0.3%P: 87.45±1.82; +D0.5%: 67.80±2.21. VD insufficiency reduced CaAbs% (-D0.5% and –D0.3% vs. +D0.5%; p<0.001) while GOS/FOS® effectiveness was negatively affected (-D0.3%P vs. +D0.3%P; p<0.001). CaAbs% of D- diets containing GOS/FOS® was improved by increasing dietary prebiotic % (-D0.3%P vs. -D0.3:2xP; p<0.01). Effectiveness of prebiotics on Ca Abs was affected by VD nutritional status.